Land, sea and home
1 online resource (488 pages)
Keywords: This book provides a realistic historical and geographical perspective to begin closest to the Scandinavian homelands of Vikings and the Viking ideology and material culture, by looking at new research into aspects of their use of the sea, maritime communications and trade.